Locality and the Prevention of Early School Leaving: Supporting Youth Transitions to Upper Secondary School in a Highly Decentralised Education System - Lisbeth Lundahl; Jonna Linde; Joakim Lindgren; Per-Åke Rosvall; Åsa Sundelin (Nordic Journal of Transitions, Careers and Guidance)
The introduction programme (IP) intends to facilitate transition to upper secondary education among Swedish youth with incomplete compulsory education. This article aims to explore and understand how local preconditions interact with schools’ support for the IP students. It looks at the local structural and institutional preconditions, and the strategies and work of head teachers, programme officers, teachers, and career counsellors, working in the IP in 90 municipalities of three categories: commuter municipalities close to big cities, rural municipalities, and small cities. The analysis builds on the responses from 139 school actors to a questionnaire, and on public statistics. On average, the commuter municipalities enjoy the most favourable structural and educational conditions, while the rural municipalities are the least resourceful, e.g. in terms of formal professional competence. Surprisingly however, the rural contexts on average perform better than the other municipalities regarding the level of graduation four years after starting the IP. There are few systematic local differences in the work with IP students. However, the IP in the rural municipalities on average enjoy higher support from school leaders, have a clearer division of responsibilities, and separate the students spatially to a lower degree compared to the commuter municipalities. Systematic handover between compulsory schools and the IP is less common in the commuter municipalities than in the other two groups. Whether these factors are relevant for explaining the higher success level in the rural schools and the lower success level in the schools in the commuter municipalities requires further investigation. Abstrakt Introduktionsprogrammet (IM) avser att underlätta övergången till gymnasieskolan bland ungdomar med låga eller ofullständiga grundskolebetyg. Syftet med artikeln är att undersöka och förstå hur lokala förutsättningar interagerar med skolornas stöd för IM-eleverna. Den analyserar de lokala strukturella och institutionella förutsättningarna, och strategierna och arbetet hos rektorer, programansvariga, lärare och karriärvägledare som arbetar med IM i 90 kommuner. Dessa tillhör kommunkategorierna pendlingskommuner nära storstäder, landsbygdskommuner och mindre städer. Analysen bygger på enkätsvar från 139 skolaktörer, och på offentlig statistik. Resultat: Pendlingskommunerna har i genomsnitt de mest fördelaktiga strukturella och utbildningsförhållandena, medan landsbygdskommunerna är minst resursstarka i dessa avseenden, t. ex. i termer av tillgänglig formell lärar- och vägledarkompetens. Därför är det förvånande att landsbygdskommunerna i genomsnitt presterar bättre än de andra kommunerna i termer av andelen elever som avlägger examen på ett nationellt gymnasieprogram fyra år efter starten på IM. Det syns få systematiska skillnader i arbetet med IM-eleverna. Emellertid har IM i landsbygdskommunerna i högre grad stöd från skolledarna och en klar ansvarsfördelning, och separerar i mindre utsträckning IM-eleverna spatialt från övriga gymnasieelever än i pendlingskommunerna. Om dessa faktorer är relevanta för att förklara de bättre resultaten i landsbygdsskolorna och de sämre i pendlingskommunerna kräver dock ytterligare undersökning. Nyckelord: ungdomsövergångar; gymnasieskolan; introduktionsprogrammet; lokal kontext